Cardiometabolic Risk in South Asian Inhabitants of California: Hypertriglyceridemic Waist vs Hypertriglyceridemic Body Mass Index - Abbasi, Fahim (Ethn Dis, 2016)
OBJECTIVE: Hypertriglyceridemic waist (HTG-waist), an increased waist circumference (WC) with an elevated triglyceride (TG) concentration, can identify increased cardiometabolic risk in apparently healthy individuals. Since WC and BMI are highly correlated, we examined whether an HTG-BMI would be as effective as an HTG-waist in identifying cardiometabolic risk in apparently healthy South Asians. DESIGN, SETTING AND PARTICIPANTS: In this cross-sectional study, we classified South Asian women (n=1156) and men (n=1842) without diabetes mellitus as having an HTG-waist (TG ≥150 mg/dL and a WC ≥80 cm in women or ≥ 90 cm in men) and an HTG-BMI (TG ≥150 mg/dL and a BMI ≥23 kg/m²). OUTCOME MEASURES: We measured cardiometabolic risk factors, including blood pressure and fasting lipid profile, glucose, insulin, fibrinogen, and high-sensitivity C-reactive protein. RESULTS: An HTG-waist was present in 670 individuals, of whom 648 (97%) had an HTG-BMI. The cardiometabolic profile was significantly more adverse in those in whom an HTG-waist was present vs absent; and the same was true when individuals with an HTG-BMI were compared with those without. CONCLUSIONS: Essentially every individual with an HTG-waist also had an HTG-BMI. An HTG-BMI identified cardiometabolic risk as effectively as an HTG-waist in a population composed entirely of South Asians.